Assessment of Drug Related Problems and Prescription Auditing in Patients Undergoing Chemotherapy for Breast Cancer in a Private Cancer Hospital: An Observational Study - Nataraj, Akash H; Morabad, Soumya Shivalingappa; Shalavadi, Mallappa Hanumanthappa; V Mangannavar, Chandrashekar; Madhabhavi, Irappa Vithoba (Indian Journal of Pharmacy Practice)
Background: Chemotherapy stands as a cornerstone in the management of breast cancer, offering substantial benefits in terms of disease control and survival outcomes. However, the complexity of chemotherapy regimens coupled with the potential for Drug-Related Problems (DRPs) underscores the importance of meticulous prescription auditing and proactive intervention to optimize treatment efficacy and safety. Aim and Objectives: Prescription auditing for patients receiving chemotherapy for breast cancer, determining the risk factors linked to breast cancer, and finding drug-related issues with chemotherapy treatments for patients with breast cancer. Materials and Methods: This is prospective observational research that lasted six months. Breast cancer patients who were above 18 years of age and were on chemotherapy along with supportive care medications were enrolled. Results: The study included 100 participants in total. The majority were in the age group of 40-60 years (n=72, 72%). Age is one of the most common risk factors in our study. Prescription auditing revealed that in (n=33, 33%) prescriptions, necessary pre-laboratory tests were not performed, and in (n=2, 2%) of patients, demographic details and dose calculation were missing during a few cycles of chemotherapy. Most commonly reported ADRs were chemotherapy-induced alopecia (n=60, 37%) and chemotherapy-induced anaemia (n=26, 16%). 61% ADRs were probable and 20% ADRs were certain according to the WHO-UMC causality assessment. Conclusion: This study underscores the importance of prescription auditing and careful monitoring of drug-related problems in breast cancer patients undergoing chemotherapy. Interventions based on these audits significantly enhance treatment safety and efficacy, potentially improving patient outcomes.
Keywords: Alopecia; Anaemia; Breast cancer; Causality assessment; Chemotherapy